ISOLATION OF PLASMID DNA FROM STREPTOMYCES SP. BACTERIA AND ESCHERICHIA COLI PBR322 TRANSFORMATION - Murtakab Y. AL-Hejjaj; Fawziah A. Abdullah; Kawther H. Mehdi (Basrah Journal of Veterinary Research)
The local Streptomyces sp. strain showed an ability to produce antimicrobial metabolite active against standard strains, in primary and secondary screening. The produced antibiotic was extracted, purified and identified as a peptide antibiotic produced about 1.4g/L in 7 days incubation period, and its LD50 was 5500. There was an inverse effect for orange acridine dye on the grown colonies number of S. sp., the 28 g/ml dye concentration was chosen as the best concentration because it led to colonies killing by 95%. Plasmid DNA extracted from S. sp. and then transformed to E. coli pBR 322, the E. coli pBR 322 showed negative results against the standard strains in primary screening before plasmid DNA transformation, while transformed E. coli pBR322 showed positive results. The antibiotic produced by trans. E. coli pBR322 was extracted, purified and identified by the same ways, which gave the same antibiotic produced by S. sp. with an increase of 2.2 g/L in the quantity and shorter period of time (2 days).